Pengaruh Penambahan Asbuton LGA 50/30 pada Campuran AC-WC dengan Inovasi Limbah Keramik sebagai Pengganti Sebagian Agregat Kasar - Setiawan, Feri Yusup; Pristyawati, Tantin; Wibawa, Satria Agung (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
Asphalt is the main ingredient in road pavement mixtures. Indonesia has relied on Pertamina to supply artificial asphalt, but the more abundant natural asphalt has not been utilized. The government is trying to encourage the use of Buton asphalt to optimize the use of natural resources. Limited natural resources also encourage innovation, such as the use of ceramic shard waste as coarse aggregate in road construction. This is important because excessive extraction of raw materials from nature can damage the ecosystem. This study analyzed the effect of adding Asbuton LGA 50/30 to AC-WC with ceramic waste. The method used was experimental with Marshall characteristic parameters. The research results from 5 variations of ceramic waste mixture used with variation values of 10%, 15%, 20%, 25%, and 30%. The highest stability was found in the 10% ceramic waste mixture with a stability value of 1178.14 kg, with a VIM value of 5.05%, VMA value of 17.87%, VFA value of 71.94%, flow value of 2.24 mm, and MQ value of 799.51 kg/mm. The 11% abuton variation level has the highest stability value found in the 10% ceramic variation with the highest stability value of 1660.90 kg, VIM value of 4.97%, VMA value of 16.08%, VFA value of 69.16%, flow value of 2.22 mm, and MQ value of 753.22 kg/mm. Both variants are declared the most effective for AC-WC asphalt mixtures because their Marshall values are in accordance with Bina Marga 2018 specifications, and the ceramic waste variation is the most effective for AC-WC asphalt mixtures